A Study Into The Factors That Have The Greatest Effect On Job Satisfaction For North Carolina Paramedics - Vipperman, Raymond, III (My University, 2019)
This study seeks to determine which factors have the greatest influence on paramedic job satisfaction. More specifically, it seeks to determine if intrinsic or extrinsic factors have the greater effect. Additionally, the effects of education on paramedic job satisfaction are examined. Finally, it seeks to determine if the generation to which the paramedic belongs has an effect on job satisfaction. A cross-sectional survey was utilized to assess how paramedics felt about how their organizations rated regarding various motivational factors. In addition, the surveys sought to determine the paramedics’ current level of job satisfaction. The surveys were sent to various EMS agencies in North Carolina so as to only receive results from currently employed paramedics. The Human Services Job Satisfaction Questionnaire developed by Shapiro, Burkey, Dorman, and Welker (1997) was utilized to formulate the survey. Data was collected via an online survey during the period of October to December 2018. The number of returned surveys totaled 254. Only surveys completed by paramedics were retained for analysis, which reduced the sample size to 222. Analysis revealed that both intrinsic (rs = .68, p = < .001) and extrinsic (rs = .73, p = < .001) factors had strong positive relationships with job satisfaction, with extrinsic factors being slightly stronger. Education level, while showing a minimal negative relationship, did not have a statistically significant correlation with job satisfaction (rs = -0.108, p = .111). Further analysis did reveal statistically significant differences in job satisfaction levels between education groups (X2(3) = 2.840, p = 0.014). Finally, differences in job satisfaction levels between generations did prove statistically significant (X2(4) = 12.756, p = 0.013).
INTRODUCTION 1 -- STATEMENT OF THE PROBLEM 2 -- CONCEPTUAL FRAMEWORK FOR THE STUDY 3 -- Purpose of the Study 6 -- RESEARCH QUESTIONS 7 -- Hypotheses 7 -- Procedures 8 -- Significance of Study 10 -- Limitations of This Study 10 -- Summary of the Research Layout 10 -- A REVIEW OF THE LITERATURE 12 -- Introduction to the Literature 12 -- The History of EMS 13 -- Early Military History 13 -- The Civil War and Beyond 15 -- Early Civilian Emergency Medical Services 17 -- Modern EMS: 1960 to Today 18 -- Paramedic Education 22 -- Job Satisfaction 24 -- Employee Motivation 26 -- The Origins of Motivation 27 -- Classical Studies of Motivation 27 -- Intrinsic and Extrinsic Motivators 38 -- Public Service Motivation 40 -- Education’s Effect on Motivation 44 -- Generational Differences 45 -- Summary 46 -- METHODOLOGY 48 -- OVERVIEW 48 -- Instrumentation 52 -- Validity 53 -- Participants 54 -- Outcome Variables 54 -- Dependent Variable 54 -- Independent Variables 55 -- Demographics 56 -- Data Analysis 57 -- Ethical Considerations 59 -- Summary 59 -- CHAPTER IV 60 -- RESULTS 60 -- OVERVIEW 60 -- Sample Overview 60 -- Exploratory Questions 62 -- Primary Question 62 -- Secondary Question Number 2 65 -- Summary 67 -- CONCLUSION 68 -- Summary 68 -- DISCUSSION OF THE RESULTS 69 -- Primary Research Question 69 -- Do intrinsic or extrinsic factors have the greater effect on paramedic job satisfaction? 69 -- Secondary Research Questions 71 -- Does a higher educational level affect the job satisfaction of the paramedic? 71 -- Does a paramedic’s generation affect the level of perceived job satisfaction? 73 -- Implications for the Field of EMS 74 -- Public Administration Theory 76 -- Limitations of Study 77 -- Recommendations for Future Research 77 -- Conclusion 78 -- APPENDIX A 90 -- JOB SATISFACTION SURVEY 90 -- APPENDIX B 101.
Keywords: Dissertations, Academic--United States; Emergency medical technicians; Emergency medical services; Job satisfaction; Surveys; North Carolina